2017
DOI: 10.1016/j.scitotenv.2017.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of root components of celery on pyrene bioaccessibility, soil enzymes and microbial communities in pyrene and pyrene-diesel spiked soils

Abstract: Though phytoremediation is deemed as a promising approach to restore polycyclic aromatic hydrocarbon (PAHs) contaminated sites, studies about how the biodegradation of PAHs is enhanced still remains incomprehensive. Effects of root components on pyrene bioaccessibility, soil enzymes and microbial communities were explored in the paper, and their interactions in simulated pyrene and pyrene-diesel spiked microcosms were tried to give a reasonable explanation. Results indicated that root components enhanced the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Pyrene is a polycyclic aromatic hydrocarbon (PAH) which may be produced commercially to be utilized as an intermediate in the production of pigments or it can be found in emissions of incomplete combustion of kerosene and diesel. The crystalline structure of pyrene (C 16 H 10 ) is a four-ring PAHs that is solid at room temperature due to different neutrons 1,2 . The long-term and continuous emission of PAHs into the environment can pose a serious threat to human health and environment through air pollution or soil contamination pathways, e.g., through industrial discharges and some agricultural tradi-tions and improper practices of waste disposal 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrene is a polycyclic aromatic hydrocarbon (PAH) which may be produced commercially to be utilized as an intermediate in the production of pigments or it can be found in emissions of incomplete combustion of kerosene and diesel. The crystalline structure of pyrene (C 16 H 10 ) is a four-ring PAHs that is solid at room temperature due to different neutrons 1,2 . The long-term and continuous emission of PAHs into the environment can pose a serious threat to human health and environment through air pollution or soil contamination pathways, e.g., through industrial discharges and some agricultural tradi-tions and improper practices of waste disposal 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2018) reported that crude-oil contamination increased soil pH, which in turn significantly decreased soil nutrient availability and α diversity of soil microbial community. Thus, biochar amendment induced high soil pH could significantly affect the phytoremediation efficiency, soil nutrient content and abundance and diversity of soil microbial community (Fernandez et al, 2014;Ghosh et al, 2014;Fernanda et al, 2017;Wei et al, 2017;Hussain et al, 2018). In the present study, biochar and compost were co-amended and resulted in a significant increase in soil nutrient content, OTU number, OTU abundance and diversity indices of soil microbial community, but soil pH decreased as compared with the biochar amendment.…”
Section: Discussionmentioning
confidence: 51%
“…3). Soil DHA and PPO are important oxidoreductases related to the biodegradation of alkanes and aromatics (Tang et al, 2010;Wei et al, 2017). The increased soil DHA and PPO activities indicate the enhanced soil microbial activity (Wang et al, 2015), as demonstrated by the abundance and diversity of soil bacterial and fungal communities (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Plants useful in PAH removal from soil also include Mariscus alternifolius and Fimbristylis ferruginea [86]; Festuca arundinacea, F. elata and F. gigantea [80]; and Hylotelephium spectabile [87]. A significant role of plants in the phytoremediation of petroleum-based pollutants was also confirmed by Jing et al [100] and Iqbal et al [37]. The transformation of hydrocarbons was also dependent on their structure and properties, i.e., faster degradation was observed for those with a simpler structure than for the more complex ones.…”
Section: Degradation Of Hydrocarbonsmentioning
confidence: 70%